Performance evaluation of renewable-based sustainable micro-grid under predictive management control strategy: A case study of Gado refugee camp in Cameroon - Same, Noel Ngando; Yakub, Abdulfatai Olatunji; Kigha Nsafon, Benyoh Emmanuel; Owolabi, Abdulhameed Babatunde; Mih, Thomas Attia; Suh, Dongjun; Huh, Jeung-Soo (Frontiers in Energy Research, 2022)
The recent use of hybrid renewable energy systems (HRESs) is considered one of the most reliable ways to improve energy access to decentralized communities because of their techno-economic and environmental benefits. Many distant locales, such as camps in war-torn nations, lack basic necessities like power. This study proposes a remedy for power outages in these areas; by designing an HRES and a control system for monitoring, distributing, and managing the electrical power from sustainable energy sources to supply the load. Hence, providing affordable, reliable, and clean energy for all (Sustainable Development Goal 7). In this study, the feasibility and techno-economic performance of an HRES for a refugee camp was evaluated under load following (LF), cycle charging (CC), and predictive control strategy (PS). The optimization results revealed that the PS was the most suitable, as it had the lowest cost and was more eco-friendly and energy-efficient. The predictive control strategy had a 48-h foresight of the load demand and resource potential and hence could effectively manage the HRES. The total net present cost (NPC) for the electrification of this refugee camp was 3,809,822.54, and the cost of electricity generated for every kWh is 0.2018. Additionally, 991,240.32 kg of emissions can be avoided annually through the hybridization of the diesel generator under the PS.